PENERAPAN TEKNOLOGI BIOFLOK PADA USAHA LELE UNTUK MENINGKATKAN EKONOMI MASYARAKAT DESA BUKET KECAMATAN KUTA MAKMUR - yuli asbar; Iswadi Iswadi; Erlangga Erlangga; Fitri Al Faini Siregar (LPPM Universitas Al Muslim, 2022)
Community service activities are focused on guidance villages that will increase catfish production and innovation in organic catfish cultivation. The main targets of this activity are: 1) the creation of a biofloc catfish pond, 2) self-reliance in the manufacture of seeds and feed, 3) the cultivation of organic catfish with biofloc pond technology. Problems faced with partners include there is no biofloc catfish pond and its installation, partners do not understand about technology in rapidly increasing catfish production, and knowledge of group development business in business management is still limited. Based on the situation analysis, the objective conditions that exist with the partners, the solutions that are mutually agreed upon between the team and partners include 1) The existence of biofloc technology for catfish pond 2) Briefing on how to make catfish feed; and 3) business management and institutional training. The purpose of this activity is to increase the quantity of catfish production. and increasing production cost efficiency through the dissemination of biofloc technology in the catfish business. Method The activity will be carried out involving two stages which include 1) socialization and coordination of activities; 2) design and manufacture of biofloc ponds, 3) operational testing in traditional manufacturing; 4) dissemination of technology products; and 5) operational assistance. In this activity, both partners were given training on operating techniques and manufacturing installation techniques for making biofloc ponds, techniques, and product marketing business strategies. The results of this community service is the partners can apply a biofloc system and provide results to improve water quality in catfish farming, then provide optimal growth for catfish.